2006
DOI: 10.1177/0306624x05283529
|View full text |Cite
|
Sign up to set email alerts
|

Treating Sexual Offenders With Learning Disabilities in the Community

Abstract: This study offers a critical review of a treatment group for sexual offenders with learning disabilities. The participants were diverted from criminal proceedings due to their level of cognitive functioning and attended a 7-month treatment program comprising of four main components: sex education, cognitive distortions, offending cycle, and relapse prevention. A number of psychometric assessments were administered immediately before and after intervention. Although no significant differences were found in atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 43 publications
1
65
1
Order By: Relevance
“…Treatment programs for sex offenders with IDD were implemented in a variety of settings and nations including prisons, hospitals, assisted living arrangements, and private homes in the United Kingdom, the United States, New Zealand, and Australia. Twelve studies were conducted in the United Kingdom (Craig et al, 2006; Craig et al, 2012; Lindsay, Marshall, et al, 1998; Lindsay, Neilson, et al, 1998; Lindsay et al, 2011; Lindsay et al, 1999; Lindsay & Smith, 1998; Michie & Lindsay, 2012; Murphy et al, 2007; Murphy et al, 2010; Rose et al, 2002; Rose et al, 2012), three studies were conducted in Australia (Keeling et al, 2006b, 2007; O’Connor, 1996), two in the United States (Rea et al, 2014; Singh et al, 2011), and one in New Zealand (Sakdalan & Collier, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…Treatment programs for sex offenders with IDD were implemented in a variety of settings and nations including prisons, hospitals, assisted living arrangements, and private homes in the United Kingdom, the United States, New Zealand, and Australia. Twelve studies were conducted in the United Kingdom (Craig et al, 2006; Craig et al, 2012; Lindsay, Marshall, et al, 1998; Lindsay, Neilson, et al, 1998; Lindsay et al, 2011; Lindsay et al, 1999; Lindsay & Smith, 1998; Michie & Lindsay, 2012; Murphy et al, 2007; Murphy et al, 2010; Rose et al, 2002; Rose et al, 2012), three studies were conducted in Australia (Keeling et al, 2006b, 2007; O’Connor, 1996), two in the United States (Rea et al, 2014; Singh et al, 2011), and one in New Zealand (Sakdalan & Collier, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…These authors reported no reoffending at one year follow-up. The difficulties associated with treatment evaluations in this 26 client group is illustrated by a treatment study of six sex offenders with ID by Craig, Stringer and Moss (2006). Following a seven month treatment programme incorporating cognitive behavioural aspects and sex education, they found no significant improvements on any measure including assessments of sexual knowledge.…”
Section: Sexual Offending and Inappropriate Sexual Behaviourmentioning
confidence: 95%
“…Others have reported similar successful behavioural programmes for this group (Grubb-Blubaugh, Shire, and Baulser, 1994;Haaven, Little, and PetreMiller, 1990) but one of the difficulties in long-term evaluation of these systems is that participants continue to be monitored and managed on a 24-hr basis by staff. This was illustrated by a treatment study of six sex offenders with ID by Craig, Stringer, and Moss (2006). Following a 7-month treatment programme incorporating sex education, addressing cognitive distortions, reviewing the offence cycle and promoting relapse prevention, they found no significant improvements on any measures including assessment of sexual knowledge.…”
Section: Inappropriate Sexual Behaviour and Sexual Offendingmentioning
confidence: 99%